Kwestie francuskiej pomocy wojskowej dla republik zakaukaskich w latach 1919-1921 - Olszewski, Paweł (Acta Universitatis Lodziensis. Folia Historica, 1999)
The article presents the French plans of deliveries of arms for independent Georgia, Armenia and Azerbaijan. The very beginning of them are connected with the appeals of the representatives of those states to the French government for acceptance of the purchase of arms in France. During the period of the defeats of Denikin’s army, at the beginning of 1920 and after the sovietisation of Azerbaijan in the end of April of that year, French and the other allies were considering the possibility of sending to Armenia and Georgia the arms that was former intended for the Denikin’s „volunteers” and the armament delivered to them by defeated Bulgaria. Eventually in autumn 1920 Georgia and Armenia were supplied with some arms, that were not from the French stock and only partially satisfied the needs of their troops.France once more considered the question of deliveries of armament for Georgia after the sovietisation of Armenia at the beginning of December 1920. But also those plans were not realised.On March 1921 the question ceased to exist because of the conquest of Georgia by Bolsheviks. On of the main causes of the failure of these projects was their second importance for the policy and military activity of France, which was concentrated on a military aid for Poland and Czechoslovakia.